Apakah Kesenangan Konsumen Dan Identifikasi Sosial Meningkatkan Loyalitas Merek? Peran Cinta Merek Sebagai Pemediasi - Harmanda Berima Putra; Kristina Anindita Hayuningtias (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Research examines the effect of customer delight, and self-identification on loyalty through the mediating role of brand love. This study uses a quantitative method with a sample of users of body care products. Data collection used an online survey method with a total of 197 respondents. The results of the analysis using SEM Amos have shown that consumer pleasure has no positive effect on brand love. Brand love has no positive effect on loyalty, customer social identification has a positive effect on love and loyalty. Furthermore, consumer pleasure has a positive effect on loyalty. Keywords: Customer delight, Social identification, Loyalty, Brand love.